Internal Audit in the function of preventing corruptive activities in the public sector of the Federation of Bosnia and Herzegovina (The Journal of Forensic Accounting Profession, 2025)
The public sector of the Federation of Bosnia and Herzegovina (FBiH) from the aspect of complexity and comprehensiveness, includes all levels of government established within the state government, public companies, and the insurance system including: pension, health and social. The importance of performing duties and obligations in a transparent manner, and the possibility of detecting warning factors for corrupt activity are especially important in the public sector. Corrupt activities at all levels of the state structure of Bosnia and Herzegovina (BiH), as well as fraudulent behaviour and abuses within it, are precisely the consequences of the complexity of the state system, and the impossibility of efficient and rational use of public funds. Adequately organized, in accordance with the law, and accepted as such by employees within a certain public sector organization, internal auditing contributes to more efficient operations and prevention of corrupt practices. The aim of the subject research is to look at the process of functioning of the internal audit in the public sector of FBiH in the field of prevention of corrupt activities. The results of the research indicate the non-functioning and non-establishment of the internal audit in the manner specified by law, as well as the inadequate implementation of its recommendations, degrading and derogating its role, importance and contribution in the prevention of corrupt activities in the public sector of FBiH.(Previously published on Sciendo: hhttps://sciendo.com/article/10.2478/jfap-2024-0002, pod licencom CC BY-NC-ND 4.0)
Keywords: internal control; internal audit; prevention; corrupt activity; public sector